Microcomputer application in measurement and control of fermentation process - Ahmad, Arshad; Jones, Meirion G (1989)
The application of microcomputer in measurement and control of biotechnological processes is gaining in popularity. In relation to this, an automation system was developed for the operation of a laboratory pilot scale stirred tank fermenter. The package employed a software interrupt function to create background execution for data acquisition and control operations whilst allowing other tasks being carried out in the foreground. The system was tested by controlling dissolved oxygen concentration employing a three term controller and good control operatis were achieved.